Identification Of Jasmani Physical Fitness Through (TKJI) Children Age 10-12 Years In Class V Students Of SD Inpres Bertingkat Kelapa Lima 1, 2 And 3 Kupang Cities - yudabbirul arif (UNIB Press, 2020)
The problem in this study is how the level of physical fitness through the Indonesian Physical Fitness Test (TKJI) in fifth-grade students of SD Lima Inpres Kelapa Lima 1, 2, and 3 Kupang City. The purpose of this study is the purpose of this study was to determine the identification of the level of physical fitness at the age of 10-12 years through the Indonesian Physical Fitness Test (TKJI) in fifth-grade students of SD Lima Negeri 5, 2 and 3 Levels in Kupang City. the type of research used in this study is descriptive as for the sample used in this study are elementary school students with five coconut levels I, II, and III in class V, amounting to 67 samples. Data collection is done by observation techniques and measurement tests and documentation of data collected and further processed using a descriptive statistical analysis technique that aims to determine the final conclusions of one study. The results of the research show that the Identification of Physical Fitness Levels (TKJI) for children aged 10-12 years in fifth-grade students of SD Lima Madras Graded 1, 2 and 3 Kupang City get the level of physical fitness of Indonesia (TKJI) children aged 10-12 years get improved the level of fitness is good with a 40m running presentation with an average score of 6.9881 in the good category, pull-ups are at a good level with an average score of 3.3333, sit-ups are at a good level with an average score of 16.00, vertical jumps are at a good level with an average score of 2.4929